Clinical analysis of 78 pulmonary sarcomatoid carcinomas with surgical treatment. Issue 10 (October 2022) - Gong, Ting; Jia, Bin; Chen, Chen; Zhang, Zhenfa; Wang, Changli
Objective: To evaluate clinical factors influencing the postoperative pulmonary sarcomatoid carcinoma (PSCs) prognosis. Methods: We retrospectively evaluated patients with PSCs treated from October 2012 to October 2017. Kaplan–Meier survival curves were calculated using univariable analysis (log-rank test). Univariable/multivariable Cox regression analysis was also performed. Results: Mixed PSCs were most common (64.10%). Pure PSCs occurred more often with large tumors compared with mixed PSCs. Patients with vs without pleural retraction, respectively, had significantly worse overall survival (OS; 16 vs 23 months) and disease-free survival (DFS; 11 vs 20 months), and patients with airway dissemination had significantly shorter OS (14 vs 21 months) and DFS (11 vs 20 months). Patients with PSC with an adenocarcinoma component had favorable OS. Airway dissemination, pleural retraction, metastatic mediastinal lymph node (LN) number, and pathological tumor-node-metastasis (pTNM) stage were risk factors for short OS. Neither adjuvant chemotherapy nor adjuvant radiotherapy provided a survival advantage. Airway dissemination was an independent prognostic factor (odds ratio, 1.87; 95% confidence interval, 1.04–3.36). Conclusion: Pure PSCs were more likely with large tumors compared with mixed PSCs. Airway dissemination, pleural retraction, and metastatic mediastinal LN number were associated with OS. Airway dissemination was an independent prognostic factor.